ICT Update 93: Impacts of digitalisation for agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
In this edition, which unfortunately will be the last, recent work of CTA in promoting digitalisation for agriculture is featured, as well as the associated impacts. Over the last 20 years, ICT Update has followed and reported on the rapidly changing landscape in ICTs for agriculture and digitalisation of the sector. The definition of digitalisation for agriculture, according to The Digitalisation of African Agriculture Report, 2018–2019, “is the use of digital technologies, innovations, and data to transform business models and practices across the agriculture value chain, including production, post-harvest handling, market access, finance and supply chain management.”